(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Insulin Resistance has a major role in the pathogenesis of diabetes mellitus where there is a decrease in sensitivity in peripheral tissues. The emergence of insulin resistance, 1-2 decades precedes before the diagnosis of type 2 diabetes mellitus is established. This theory is supported by the usefulness of insulin resistance as a marker of future diabetes or the prevention of type 2 diabetes by insulin-sensitizing agents. Recently, there is evidence that has been suggested to measure insulin resistance as surrogate marker by calculated the triglyceride and glucose which is so called as “Fasting triglyceride-glucose index” or can be shorten as “TyG index”. This study reported a systematic review of association between TyG index and type 2 diabetes mellitus from various literatures to make a conclusion as a basis for further research. Methods: A literature search in EBSCOhost, ProQuest, MEDLINE, and NCBI database was performed to retrieve and review studies reporting the association between TyG index and type 2 diabetes. Results: All studies showed that higher TyG index were associated with higher type 2 diabetes (HR 4.36, 10.38, 9.54 for each). Conclusion: This systematic review provides further evidence about higher TyG index is related to higher risk of development type 2 diabetes. It represents that TyG index can predicting the risk of incident T2DM.